Optimization of spring-back in creep age forming process of 7075 Al-Alclad alloy using D-optimal design of experiment method. (June 2016) - Khamneh, Mohammad Ershadi; Askari-Paykani, Mohsen; Shahverdi, Hamidreza; Hadavi, Seyed Mohammad Mehdi; Emami, Mohammad
Graphical abstract: Highlights: A novel creep age forming apparatus is designed and used. D-optimal design of experiment is used to model and optimize creep age forming process. Mathematical model for spring-back is presented. An appropriate region for optimized spring-back and mechanical properties for 7075 Al-Alclad alloy is presented. Abstract: This paper attempts to model and predict the spring-back for creep age forming of a 7075 Al-Alclad alloy using statistical analyses based on a design of experiments method. Time and temperature were chosen as effective variables for determining spring-back in the creep age-forming process. The D-optimal design of experiments method facilitated statistical analyses and the extraction of a mathematical model for determining spring-back in the experimental variables domain. The spring-back of the specimens was calculated using a numerical procedure based on the pure bending theory. Analysis of the variances for spring-back showed that temperature was the most effective variable in the creep-age forming process. Additionally, a mathematical model and the response surface of the spring-back showed that to decrease spring-back, the significant variables should be in the upper level. The spring-back in the creep age-forming process was optimized for a 7075 Al-Alclad alloy in the optimum mechanical properties region.